Game Edukasi Menyusun Nama Hewan Sebagai Media Pembelajaran Anak-Anak Menggunakan Construct 2 - Pontoh, Iftahul Farhan; Mustofa, Yasin Aril; Lamasigi, Zulfrianto Yusrin (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2025)
This research aims to develop an educational game to provide alternative learning and knowledge about animals and their types. The problem faced is the lack of interest and understanding of children's conventional learning materials that tend to be monotonous and non-interactive, which often results in decreased motivation to learn at home and school. To overcome this problem, an educational game application using Construct 2 software. The stages include system testing, development, construction, design, and analysis. This research takes place at SD Negeri 03 Kabila, engaging 30 students as respondents. The assessment of the game is carried out through a questionnaire analyzed descriptively and qualitatively to assess the feasibility of the application. The test results show that the application is free from component errors based on Black Box testing and is well received by users based on User Acceptance testing with a total score of 86.4%, categorized as very good. However, the random system used to generate the questions reappears which can reduce the variety and effectiveness of learning. The improvements to this system are proposed to enhance the learning quality. The development of this educational game application can be an effective solution to increase children's interest and understanding in learning while providing a fun learning experience while providing a fun and interactive learning experience.Keywords: educational game, Construct 2, animal recognition